Certain Classes of Meromorphic p-Valent Functions Associated with Mittag-Leffler Function: Certain Classes of Meromorphic p-Valent Functions - Aouf , M. K.; Mostafa, A. O.; Madian, S. M. (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this paper, using definition of subordination and Mittag-Leffler function we introduce classes of p-valent meromorphic functions and obtain some subordination results for these classes.